Shaping socio-critical thinking of junior students using problem-based learning and inquiry strategy - Muhamad Basyrul Muvid; Yudi Septiawan; Maulana Arafat Lubis; Husniyatus Salamah Zainiyati (International Journal of Evaluation and Research in Education (IJERE), 2022)
This research examined a pattern of integration between problem-based learning (PBL) strategy with inquiry in shaping the critical thinking framework and psychosocial of youth-level students. This study used a qualitative descriptive approach with a literature study method. The data sources were derived from documentation, books, and various related articles. Its analytical techniques used deductions, induction, interpretation, and comparison and analysis of multilayered texts. The results of this research showed that the PBL and inquiry strategies had substantial collation and synergy in the process of forming a framework of critical thinking and psychosocial of youth-level students. It was based on the process of implementing both strategies that emphasized the search for solutions to the problems encountered by conducting investigations, hypotheses, testing, data mining supported by teamwork, collaboration, communication, discussion, and coordination. Thus, the use of the PBL strategy and inquiry integratively is highly recommended in the learning process.